PERCOBAAN PEMUTIBAN TEPUNG SAGU (METROXYLON SP.) DENGAN KAPORIT - Abdul Hakim Lukman (Jurnal Penelitian Hasil Hutan, 1991)
The  effect   of  the  bleaching  of  sago flour  by  calcium  hypochlorite   solution   at several  concentration levels (0;  1,5; 2,0; and 2,5 percent)   and soaking  time  (30,  45,  and  60 minutes)  on sago flour  quality  were studied  at the Forest Product Research  and Development  Centre  Laboratory   in Bogor.  Results  showed   that  unbleached   sago flour  when  soaked  for  60. minutes  gave the  highest  yield  (89.48  percent).   At   1.5 percent   hypochlorite  concentration  and  30 minutes  soaking  time, the proximate   analysis  including  moisture,  ash, fat,  starch,  protein   and crude fiber  contents  are consecutively  9.34,  0. 5, 0.28,  87.60,  0.56,  and  0. 74 percent.                Application    of  1.5 percent   calcium  hypochlorite  concentration  and  30  minutes  soaking  time  could  improved pH value  (7. 70),  whiteness   (83.60 percent)   organoleptic color test  (5.04),  and organoleptic odor  test  (4.20),  while viscosity  (17.85  cP), and reduced  melanin  content   down   to  o. 05 percent.